Notes on using geostatistical software variowin. Part II: modeling the experimental variogram - Santamaría, Mariana S. (2012)
A fundamental step in all geostatistical study is the structural analysis that includes experimental variogram calculation and modeling. Modeling process consists on fitting a known theoretical model to the variogram in order to describe how the phenomenon under study behaves at those locations where it has not been sampled. In a previous paper (Part I) a detailed introduction to the exploration and calculation of variogram using Variowin 2.21 software package was provided. This paper aims to show, mainly, how to use the program Model of Variowin 2.21. Model allows fitting in an interactive way some theoretical models to experimental variogram obtained with program Vario2D. Variowin is a very good complement of other geostatistical programs which include modeling of experimental variogram.